2016
DOI: 10.1038/nature18323
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting direct reprogramming from fibroblast to neuron using single-cell RNA-seq

Abstract: Direct lineage reprogramming represents a remarkable conversion of cellular and transcriptome states1–3. However, the intermediates through which individual cells progress are largely undefined. Here we used single-cell RNA-seq4–7 at multiple time points to dissect direct reprogramming from mouse embryonic fibroblasts (MEFs) to induced neuronal (iN) cells. By deconstructing heterogeneity at each time point and ordering cells by transcriptome similarity, we find that the molecular reprogramming path is remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
431
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 420 publications
(487 citation statements)
references
References 42 publications
41
431
4
Order By: Relevance
“…In this case, the hematopoietic stem and progenitor GRNs transiently appear at the population level during the course of conversion . In addition, a recent report demonstrated that Ascl1, a neural pioneer factor, activates a neural progenitor-like state and myogenic program when overexpressed in fibroblasts (Treutlein et al, 2016). Although these engineered cell populations might not represent bona fide embryonic progenitors, it is nonetheless clear that they exist due to the engagement of developmental programs at some level.…”
Section: Understanding Pioneer Factor-driven Direct Lineage Conversiomentioning
confidence: 99%
“…In this case, the hematopoietic stem and progenitor GRNs transiently appear at the population level during the course of conversion . In addition, a recent report demonstrated that Ascl1, a neural pioneer factor, activates a neural progenitor-like state and myogenic program when overexpressed in fibroblasts (Treutlein et al, 2016). Although these engineered cell populations might not represent bona fide embryonic progenitors, it is nonetheless clear that they exist due to the engagement of developmental programs at some level.…”
Section: Understanding Pioneer Factor-driven Direct Lineage Conversiomentioning
confidence: 99%
“…5 days after expression of Ascl1 in MEFs, a subset of cells show enriched expression of pan-neuronal genes and are transcriptionally similar to neural progenitors. Similarly, the transcriptional profile of bamd22 cells, which mostly adopt a iN phenotype [12], is closely related to P7 cerebral cortex neurons. In contrast, lineage-reprogrammed MEFs that express low levels of pan-neuronal genes showed enriched expression of fibroblast genes or muscle-cell genes, indicating that those two populations represent MEFs that failed to undergo lineage-conversion or followed an alternative fate [12].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the transcriptional profile of bamd22 cells, which mostly adopt a iN phenotype [12], is closely related to P7 cerebral cortex neurons. In contrast, lineage-reprogrammed MEFs that express low levels of pan-neuronal genes showed enriched expression of fibroblast genes or muscle-cell genes, indicating that those two populations represent MEFs that failed to undergo lineage-conversion or followed an alternative fate [12]. We also show that three different populations of ascl1d5 cells can be distinguished based on their transcriptional profiles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations